자원 제약적 기기에서 자율주행의 실시간 객체탐지를 위한 태스크 오프로딩 적용에 관한 연구 - 장신원; Jang Shin Won; 홍용근; Yong-geun Hong (정보처리학회논문지. KIPS transactions on computer and communication systems. 컴퓨터 및 통신 시스템, 2023)
도로와 주변의 상황을 정확히 인지하는 객체탐지 기술은 자율주행 분야에 핵심적인 기술이다. 자율주행 분야에 객체탐지 기술은 추론 서비스의 정확도와 함께 실시간성도 요구된다. 고성능 머신이 아닌 자원제약 기기에서 정확도와 함께 실시간성을 위한 객체탐지 기술을 적용하기 위해서는 태스크 오프로딩 기술을 활용해야 한다. 본 논문에서는 자원 제약적 기기에서 자율주행의 실시간 객체탐지를 위한 태스크 오프로딩 적용과 관련하여 태스크 오프로딩의 성능 비교, 입력 이미지 해상도에 따른 성능 비교, 카메라 객체 해상도에 따른 성능 비교 등의 실험을 수행하고 결과를 분석하였다. 본 실험에서 낮은 해상도의 이미지는 태스크 오프로딩 구조의 적용을 통하여 성능 개선을 도출할 수 있었고, 이는 자율주행의 실시간 기준을 충족하였다. 높은 해상도의 이미지는 성능 개선은 있었으나 통신 시간의 증가에 따른 이유로 자율 주행의 실시간 기준을 충족하지 못하였다. 이러한 실험을 통해 자율주행에서의 객체인식은 사용하는 객체인식 모델과 함께 입력 이미지, 통신 환경 등의 다양한 조건이 영향을 미친다는 것을 확인할 수 있었다. Object detection technology that accurately recognizes the road and surrounding conditions is a key technology in the field of autonomous driving. In the field of autonomous driving, object detection technology requires real-time performance as well as accuracy of inference services. Task offloading technology should be utilized to apply object detection technology for accuracy and real-time on resource-constrained devices rather than high-performance machines. In this paper, experiments such as performance comparison of task offloading, performance comparison according to input image resolution, and performance comparison according to camera object resolution were conducted and the results were analyzed in relation to the application of task offloading for real-time object detection of autonomous driving in resource-constrained devices. In this experiment, the low-resolution image could derive performance improvement through the application of the task offloading structure, which met the real-time requirements of autonomous driving. The high-resolution image did not meet the real-time requirements for autonomous driving due to the increase in communication time, although there was an improvement in performance. Through these experiments, it was confirmed that object recognition in autonomous driving affects various conditions such as input images and communication environments along with the object recognition model used.